Respiratory Chain Supercomplexes: Structures, Function and Biogenesis - Lobo-Jarne, Teresa (Semin Cell Dev Biol, 2017)
Over the past sixty years, researchers have made outmost efforts to clarify the structural organization and functional regulation of the complexes that configure the mitochondrial respiratory chain. As a result, the entire composition of each individual complex is practically known and, aided by notable structural advances in mammals, it is now widely accepted that these complexes stablish interactions to form higher-order supramolecular structures called supercomplexes and respirasomes. The mechanistic models and players that regulate the function and biogenesis of such superstructures are still under intense debate, and represent one of the hottest topics of the mitochondrial research field at present. Noteworthy, understanding the pathways involved in the assembly and organization of respiratory chain complexes and supercomplexes is of high biomedical relevance because molecular alterations in these pathways frequently result in severe mitochondrial disorders. The purpose of this review is to update the structural, biogenetic and functional knowledge about the respiratory chain supercomplexes and assembly factors involved in their formation, with special emphasis on their implications in mitochondrial disease. Thanks to the integrated data resulting from recent structural, biochemical and genetic approaches in diverse biological systems, the regulation of the respiratory chain function arises at multiple levels of complexity.